Determination of productivity of milking cows and emissions of greenhouse gases from organic waste with different approaches to the organization of the technology of their feeding - Zolotarov, Andriy; Piskun, Viktor; Pilipcenko, Angrej; Rudenko, Evqen; Zolotarova, Svitlana; Trishin, Aleksei; Yatsenko, Yuriy (Eastern-European Journal of Enterprise Technologies, 2021)
The analysis of approaches to reduce the consumption of fodder protein and greenhouse gas emissions from organic waste in milk production is carried out, and the need to determine these indicators for various approaches to organizing the technology of their feeding is established. An increase in the content of difficult-to-digest protein in the diets of high-yielding cows made it possible to reduce greenhouse gas emissions per head per day by 14.12 % in CO2 equivalent when using 1.5 kg of TEP-mix in the ration of cows. When using 1.0 kg of TEP-mix, this figure was 6.44 %. In terms of 1 kg of milk with basic fat content, these indicators are 26.72 % and 12.98 %, respectively. A multicriteria analysis of milk production with different approaches to organizing the technology of feeding dairy cows and, in particular, when using the additive TEP-mix with a protected protein showed a significant advantage of research option No. 1 (1.5 kg of TEP-mix). For it, the objective function according to the considered criteria is the smallest and amounts to 0.039 in comparison with the idealized variant. At the same time, the target function of the control variant (without TEP-mix) is 2.67 times worse, and for the experimental variant No. 2 (1.0 kg of TEP-mix) this indicator is 2.12. The use of TEP-mix in feeding cows provided an increase in their milk productivity, milk fat and protein content and, as a result, the profitability of milk production. The studies have found that the use of the proposed approaches to the organization of the technology of feeding cows provides an increase in their productivity, a decrease in the cost of feed protein and an improvement in environmental protection. According to the authors, this is due to an increase in the content of difficult-to-digest protein in the diets of high-yielding cows